Aplikasi Dosis Pupuk Kalium Terh Aplikasi Dosis Pupuk Kalium Terhadap Pertumbuhan Dan Hasil Beberapa Genotipe Cabai Merah Lokal (Capsicum annuum L.) Sumatera Barat: Aplikasi Dosis Pupuk Kalium Terhadap Pertumbuhan Dan Hasil Beberapa Genotipe Cabai Merah Lokal (Capsicum annuum L.) Sumatera Barat - Suliansyah, Irfan; Irawati; sari, sari susanti (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2023)
In Indonesia, chili is a valuable horticultural commodity. On the other hand, chili productivity in West Sumatra shifted from time to time. One of the factors causing unstable chili production is pests. Genotype, environment, and the interaction of genotype and environment all impact plant productivity. Plant productivity increases as the environmental conditions surrounding the plant are favorable, and nutrient availability is sufficient to meet the needs of plant life. Environmental factors such as nutrient availability and genetic factors such as plant genotypes significantly impact crop production. The aim of the study was to determine the best growth and yield of several genotypes of local West Sumatra chili fertilized with potassium at various doses. The study employed a completely randomized design (CRD), 2 factor, replicated three times. The first factor was the chili genotype consisting of 6 local red chilies ie. Pesisir Selatan, Ateng Pasaman Barat, Dhamasraya 2, Ateng Maninjau, Tanah Datar and Kampung Manangah Solok Selatan. The second factor was the dose of potassium fertilizer (K2O) consisted of 180 kg/ha, 240 kg/ha and 300 kg/ha. The native chili genotype Ateng Pasaman Barat produced the highest crop yield when fertilized with potassium at a dosage of 300 kg/ha. A potassium fertilizer dose of 300 kg/ha generated the best growth and yield, as shown by higher plant height, number of fruits per plant, and fruit weight per plant. Keywords: local chili, genotype, potassium, plant growth.